ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS PADA PT SURYA ESA PERKASA TBK PERIODE 2015-2024 - Aulia, Nurul; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Surya Esa Perkasa Tbk based on profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE) during the 2015-2024 period. The research method used is descriptive quantitative, utilizing secondary data in the form of the company's financial reports. The analysis technique is carried out by calculating the ROA and ROE ratios each year and interpreting the results. The results show that the company's financial performance fluctuated during the study period, but generally experienced an increasing trend at the end of the period. This indicates that the company is able to improve the efficiency of its asset and capital utilization.